Patient-powered research networks: building capacity for conducting patient-centered clinical outcomes research. (12th May 2014) - ,; Daugherty, Sarah E; Wahba, Sarita; Fleurence, Rachael; Avillach, Paul; Buelow, Janice; Colletti, Richard; Eichler, Florian; Ginsberg, Seth; Dewitt, Esi Morgan; McBurney, Robert; Merkel, Peter A.; et al.
Abstract: The Patient-Centered Outcomes Research Institute (PCORI) recently launched PCORnet to establish a single inter-operable multicenter data research network that will support observational research and randomized clinical trials. This paper provides an overview of the patient-powered research networks (PPRNs), networks of patient organizations focused on a particular health condition that are interested in sharing health information and engaging in research. PPRNs will build on their foundation of trust within the patient communities and draw on their expertise, working with participants to identify true patient-centered outcomes and direct a patient-centered research agenda. The PPRNs will overcome common challenges including enrolling a diverse and representative patient population; engaging patients in governance; designing the data infrastructure; sharing data securely while protecting privacy; prioritizing research questions; scaling small networks into a larger network; and identifying pathways to sustainability. PCORnet will be the first distributed research network to bring PCOR to national scale.